Process intensification strategies for enhanced holocellulose solubilization: Beneficiation of pineapple peel waste for cleaner butanol production - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Kamble, Sanjay P.; Gaikwad, Shashank G.; Chavan, Prakash V.; Bankar, Sandip B. (Journal of Cleaner Production, 2018)
Biorefinery sector has become a serious dispute for cleaner and sustainable development in recent years. In the present study, pretreatment of pineapple peel waste was carried out in high pressure reactor using various pretreatment-enhancers. The type and concentration effect of each enhancer on hemicellulose solubilization was systematically investigated. The binary acid (phenol + sulfuric acid) at 180 degrees C was found to be superior amongst other studied enhancers, giving 81.17% (w/v) hemicellulose solubilization in liquid-fraction under optimized conditions. Solid residue thus obtained was subjected to enzymatic hydrolysis that resulted into 24.50% (w/v) cellulose breakdown. Treated solid residue was further characterized by scanning electron microscopy and fourier transform infrared spectroscopy to elucidate structural changes. The pooled fractions (acid treated and enzymatically hydrolyzed) were fermented using Clostridium acetobutylicum NRRL B 527 which resulted in butanol production of 5.18 g/L with yield of 0.13 g butanol/g sugar consumed. Therefore, pretreatment of pineapple peel waste evaluated in this study can be considered as milestone in utilization of low cost feedstock, for bioenergy production. (C) 2018 Elsevier Ltd. All rights reserved.

Solvent extraction of butanol from synthetic solution and fermentation broth: batch and continuous studies - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Gaikwad, Shashank G.; Chavan, V, Prakash; Bankar, Sandip B. (Separation and Purification Technology, 2020)
Product recovery is one of the essential finishing steps to any commercial fermentation process. In acetone-butanol-ethanol (ABE) fermentation, butanol recovery is quite tedious mainly due to dilute product and multiple byproduct formation in complex media. Among different recovery methods, extraction has attracted considerable attention in biofuel recovery owing to its high selectivity, low energy consumption, and ease of operation. In present work, the butanol extraction performance from synthetic solvent mixture containing ABE was tested in batch and continuous operations using 20% (v/v) decanol in oleyl alcohol. The optimized extraction conditions were then validated using actual fermentation broth to confirm effectiveness of the extraction operation. The distribution coefficient (K-d) and batch extraction efficiency (E) were in the range of 5.60-9.80 and 87.70-86.90% for fermentation broth and synthetic solution, respectively for a given initial concentration of butanol in the aqueous phase. Further, E was relatively improved by supplementing different inorganic salts. Sodium hydroxide (5%, w/v) was highly effective to recover butanol from fermentation broth (E similar to 97.70%) with K-d of 33.10. Besides, the continuous counter current extraction of butanol in a packed column was performed. The volumetric mass transfer coefficient (kLa) was estimated to be 0.025 1/min at an optimized superficial velocity of the aqueous phase (0.28 cm/min) and sodium hydroxide concentration (5%, w/v). Height of the extraction column was estimated to be 28.32 cm using height of transfer unit (HTU) and number of transfer unit (NTU) concept for extraction efficiency of 97.20%. Overall, the present study has demonstrated an enhanced extraction efficiency of butanol from fermentation broth.
Keywords: Biobutanol; Equilibrium stages; Height of transfer unit; liquid-liquid extraction; mass transfer coefficient; Number of transfer unit

Ultrasound assisted curcumin recovery from Curcuma aromatica: understanding the effect of different operating parameters - Shirsath, Sachin R.; Sable, Sunil S.; Gaikwad, Shashank G.; Gogate, Parag R. (Chemical Engineering and Processing-Process Intensification, 2021)
The present study deals with intensified extraction of curcumin from Curcuma aromatica by employing ultrasound-assisted extraction (UAE) approach also elucidating comparison with the conventional batch extraction to highlight the intensification benefits based on the usage of ultrasound. Understanding into the effect of operational parameters like type of solvent, extraction temperature, solid to solvent ratio and raw material size distribution as well as the equipment operating conditions as frequency and power on the extraction yield has been developed. Based on the results for extraction yield, the optimum conditions for UAE approach were 40 degrees C as temperature, 1:30 as solid to solvent ratio, 0.09 mm as the mean particle size, 240 W as ultrasonic power, 22 kHz as ultrasonic frequency and ethanol as the most suitable solvent. Under these optimum conditions, the highest extraction yield of 73.18% was achieved in 2 h whereas batch extraction for 14 h resulted in 52.31% yield clearly demonstrating the intensification due to ultrasound. Peleg's model was applied to explain the extraction kinetics of curcumin and the proposed model satisfactorily predicted the rates of extraction of cur cumin. Overall, UAE proved to be a better technique in terms of lesser time, lesser heating requirement and additional extraction yield.
Keywords: Cavitation; Curcuma aromatica; curcumin; Intensification; Kinetic modelling; Ultrasound assisted extraction

Liquid-liquid equilibria of ternary mixtures containing Aniline plus Toluene plus water at elevated temperatures: measurements and correlation - Gaikwad, Shashank G.; Pathak, Abhishek A.; Mote, Dhananjay R.; Gogate, Parag R.; Singh, Shivani; Modhera, Bharat (Separation Science and Technology, 2023)
Liquid-liquid equilibrium (LLE) data for the ternary system, Aniline + Toluene + Water, was measured at different temperatures of 298.15 K, 313.15 K and 323.15 K under atmospheric pressure with the help of High-Performance Liquid Chromatography (HPLC) analysis and Karl-Fischer technique. The efficiency of Toluene to extract Aniline from aqueous phase was then quantified in terms of the distribution coefficient and separation factor based on the tie line data. The system showed very good separation ability quantified in terms of high values of distribution factor (average around 7) and separation factors (as high as 1000). The experimental tie line data was verified by Hand and Othmer-Tobias equations. The LLE data was also correlated using NRTL and UNIQUAC models and both of them were able to represent the behavior of the system accurately when tested against experimental results. Toluene has been demonstrated to be very efficient to extract Aniline from reaction mixture, which is typically a by-product in hydrogenation of nitrobenzene, a process commercially used to produce p-Aminophenol in industry.
Keywords: Aniline; LLE; NRTL; Tie line; Toluene; UNIQUAC

Ultrasound emulsification: effect of additives on dispersed phase volume and droplet size - Gaikwad, Shashank G.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2025)
Ultrasonic emulsification of oil and water was carried out to observe the effect of addition of a minimal amount of surfactant. The effect of ultrasound irradiation time, power, and physicochemical properties of oil on the dispersed phase volume and dispersed phase droplet size has been studied. The increase in the irradiation time increases the dispersed phase volume, while it decreases the dispersed phase droplets size. With an increase in the ultrasonic irradiation power, there is an increase in the fraction of volume of the dispersed phase, while the droplet size of the dispersed phase decreases over the same irradiation time. The fractional volume of the dispersed phase is higher for the case of the groundnut oil-water system, while it is low for the paraffin (heavy) oil-water system. The droplet size of soyabean oil dispersed in water is found to be small, while that of paraffin (heavy) oil is found to be large. These variations could be explained on the basis of varying physicochemical properties of the system, i.e., viscosity of oil and the interfacial tension. During the ultrasonic emulsification, a coalescence phenomenon which is relatively weak has also been observed, which can be attributed to the collision of small droplets when the droplet concentration increases (higher dispersed phase hold-up) and the acoustic streaming strength is higher.